Augmentation of labour with synthetic oxytocin: a mixed methods study - Alòs Pereñíguez, Silvia (Trinity College Dublin. School of Nursing & Midwifery. Discipline of Nursing, 2025)
Background: Augmentation of labour with synthetic oxytocin is one of the most frequently performed childbirth interventions among women with spontaneous onset of labour. Rates of augmentation of labour with synthetic oxytocin are unknown in many countries and, where data is collected, they vary widely between countries and among maternity hospitals within the same country. To date, there is a paucity of research on women’s views and experiences of augmentation of labour with synthetic oxytocin, both internationally and in Ireland. Additionally, the prevalence and associated factors with augmentation of labour with synthetic oxytocin within the Irish context have not been examined. Aim: To achieve a greater understanding of women’s views and experiences of augmentation of labour with synthetic oxytocin internationally and in Ireland, and to estimate the prevalence and factors associated with augmentation of labour with synthetic oxytocin in Ireland. Methodology: A multistage mixed methods study was conducted. Four interlinked sequential phases were utilised to synthesise the international evidence on women’s views and experiences of augmentation of labour with synthetic oxytocin, provide a rich description of women’s experiences of augmentation of labour with synthetic oxytocin in Ireland and identify associated factors with augmentation of labour with synthetic oxytocin among women birthing within the Irish context. Phases 1 and 2 comprised the qualitative component of this mixed methods study with a qualitative evidence synthesis (n=25) and a qualitative descriptive study (n=14). Phases 3 and 4 comprised the quantitative component. The data reliability issues encountered during the data analysis of Phase 3, a national cross-sectional study (n=24,001), led to the addition of Phase 4: a single-site cross-sectional study (n=2,086). Integration occurred at two key points at the design and discussion levels. Findings: Augmentation of labour with synthetic oxytocin has a significant impact on women’s birth experiences. Regardless of the country or context, women recalled augmentation of labour with synthetic oxytocin mainly in negative terms and consistently described it as atypically painful. Most women wanted to be involved in the decision to have their labour augmented, although the meaning of feeling involved varied according to their knowledge and trust in their healthcare professionals. Concerning findings emerged in relation to informed consent where women described having their labour augmented without consent, feeling intimidated to comply and acquiesce, or giving consent without receiving enough information to give genuine informed consent. Women with limited knowledge of augmentation of labour with synthetic oxytocin and women from countries with underdeveloped maternal healthcare services showed a more favourable attitude towards having their labour augmented and seemed to accept augmentation of labour with synthetic oxytocin more readily. Some even thought that augmentation of labour with synthetic oxytocin was part of having a ‘normal’ birth, emphasising its widespread use in clinical practice. In contrast, other women who had their labour augmented felt ‘rushed’ into giving birth, with frequent references to time constraints and rigid time frames for giving birth. After the birth and over time, women moved from self-blame towards feeling betrayed by their healthcare professionals and ‘the system’. Women regretted not having asked more questions, having been too trusting of healthcare professionals and accepting to have augmentation of labour with synthetic oxytocin. In subsequent pregnancies and births, women adopted different strategies to avoid undergoing augmentation of labour with synthetic oxytocin for a second time. The prevalence of augmentation of labour with synthetic oxytocin in Ireland remains unknown. Only those findings from Phase 4 (single-site cross-sectional study) contributed data to the quantitative component. The overall prevalence of augmentation of labour with synthetic oxytocin in this phase was 18.70%. A total of 37.41% nulliparous women and 6.62% multiparous women underwent augmentation of labour with synthetic oxytocin. Nulliparity (OR 8.42, 95% CI 6.48-10.96; RR 2.60, 95% CI 2.37-2.84; p<0.001) and private care (OR 1.67, 95% CI 1.19-2.35; RR 1.58, 95% CI 1.17-2.14; p=0.004) predisposed women to undergoing augmentation of labour with synthetic oxytocin. The crude analyses demonstrated a positive association between augmentation of labour with synthetic oxytocin and instrument-assisted birth (OR 5.40, 95% CI 4.15-7.05; RR 1.54; 95% CI 1.48-1.58; p<0.001), caesarean section (OR 3.08 95% CI 2.18-4.35; RR 1.25; 95% CI 1.19-1.3; p<0.001), suspected fetal hypoxia during labour as per CTG trace or fetal scalp pH results (OR 3.80, 95% CI 2.97-4.86; RR 2.75, 95% CI 2.30-3.27; p<0.001), women having their baby admitted to NICU (OR 2.36, 95% CI 1.36-4.10; RR 2.29, 95% CI 1.35-3.89; p=0.003), postpartum haemorrhage (OR 2.11, 95% CI 1.60-2.80; RR 1.86, 95% CI 1.50-2.34; p<0.001), fetal scalp blood sampling (OR 3.99, 95% CI 2.36-6.78; RR 3.79, 95% CI 2.28-6.28; p<0.001), epidural analgesia (OR 19.81, 95% CI 14.23-27.58; RR 3.12; 95% CI 2.87-3.38; p<0.001) and episiotomy (OR 3.75, 95% CI 2.98-4.72; RR 2.37, 95% CI 2.07-2.72; p<0.001). After adjustment for potential confounders, a positive association between augmentation of labour with synthetic oxytocin and instrument-assisted birth (aOR 2.62, 95% CI 1.95-3.52; RR 1.36; 95% CI 1.26-1.44; p<0.001), caesarean section (aOR 1.99, 95% CI 1.36-2.90; RR 1.17; 95% CI 1.09-1.24; p<0.001), suspected fetal hypoxia during labour as per CTG trace or fetal scalp pH results (aOR 1.81, 95% CI 1.37-2.38; aRR 1.21, 95% CI 1.12-1.29; p<0.001), women having their baby admitted to NICU (aOR 2.01, 95% CI 1.09-3.71; aRR 1.21, 95% CI 1.03-1.34; p=0.026), fetal scalp blood sampling (aOR 2.22, 95% CI 1.25-3.94; aRR 1.34, 95% CI 1.10-1.53; p=0.007) and epidural analgesia (aOR 14.09, 95% CI 10.02-19.80; aRR 1.63; 95% CI 1.60-1.66; p<0.001). Conclusions: Augmentation of labour with synthetic oxytocin remains one of the most frequently performed childbirth interventions among women with spontaneous onset of labour, particularly among nulliparous women. The widespread use of augmentation of labour with synthetic oxytocin along with its potential significant implications on women’s birth experiences, mode of birth, further childbirth interventions, and adverse perinatal outcomes underscore the need for continued research, and reassessment of current practices and policies on this topic.
APPROVED